Application of PAUT Technology in Testing Radial Gate on the Right Bank of the Datengxia Water Conservancy Project - XIE Ji'an; PAN Hong; HE Qilian; CHEN Zhuangsheng; LIU Tao (Renmin Zhujiang)
Under the background of a tight construction schedule and heavy tasks,this paper applies PAUT technology to the radial gate on the right bank of the Datengxia water conservancy project,so as to ensure the welding quality of the radial gate of the Datengxia water conservancy project.In addition,the conventional ultrasonic testing technology and PAUT technology are used and compared in terms of the welds in the main parts of the gate.The experimental comparison results show that PAUT technology is superior to conventional ultrasonic testing technology in defect detection rate and graphic imaging.It is proved that the defect detection rate of PAUT technology is better than that of the conventional ultrasonic wave,and log files permanently saved can be obtained.